Pulp surrealism : insolent popular culture in early twentieth-century Paris - Walz, Robin, 1957- (University of California Press, 2000)
In addition to its more well known literary and artistic origins, the French surrealist movement drew inspiration from currents of psychological anxiety and rebellion running through a shadowy side of mass culture, specifically in fantastic popular fiction and sensationalistic journalism.